Rate, determinants, and causes of stillbirth in Jordan: Findings from the Jordan Stillbirth and Neonatal Deaths Surveillance (JSANDS) system - Shattnawi, Khulood K. (BMC Pregnancy Childbirth, 2020)
BACKGROUND: Annually, 2.6 million stillbirths occur around the world, with approximately 98% occurring in low- and middle-income countries. The stillbirth rates in these countries are 10 times higher than the rates in high-income countries. METHODS: An electronic stillbirths and neonatal deaths surveillance system (JSANDS) was established in five large hospitals located in three of the largest cities in Jordan in August 2019. JSANDS was developed as a secure on-line data entry system to collect, organize, analyze, and disseminate data on stillbirths, neonatal deaths, and their contributing conditions. Data on births, stillbirths and their contributing conditions, and other demographic and clinical characteristics in the period between August 2019 – January 2020 were extracted and analyzed. RESULTS: A total of 10,328 births were registered during the reporting period. Of the total births, 102 were born dead (88 antepartum stillbirths and 14 intrapartum stillbirths), with a rate of 9.9 per 1000 total births. The main contributing fetal conditions of antepartum stillbirths were antepartum death of unspecified cause (33.7%), acute antepartum event (hypoxia) (33.7%), congenital malformations and chromosomal abnormalities (13.3%), and disorders related to the length of gestation and fetal growth (10.8%). The main contributing maternal conditions of antepartum stillbirths included complications of the placental cord and membranes (48.7%), maternal complications of pregnancy (23.1%), and maternal medical and surgical conditions (23.1%). Contributing fetal conditions of intrapartum stillbirths included congenital malformations, deformations and chromosomal abnormalities, other specified intrapartum disorders, and intrapartum death of unspecified cause (33.3% each). Contributing maternal conditions of intrapartum stillbirths included complications of the placental cord and membranes. In the multivariate analysis, small for gestational age (SGA) pregnancies were associated with a significant 3-fold increased risk of stillbirth compared to appropriate for gestational age (AGA) pregnancies. CONCLUSIONS: Although the rate of stillbirth is lower than that in other countries in the region, there is an opportunity to prevent such deaths. While the majority of stillbirths occurred during the antepartum period, care should be taken for the early identification of high-risk pregnancies, including the early detection of SGA pregnancies, and ensuring adequate antenatal obstetric interventions.